Application of the lateral angle method for sex determination of cremated individuals from burials of the Lusatian culture cemetery in Czernikowice, Poland - Hałuszko, Agata; Guziński, Maciej (Anthropological Review, 2022)
Research of cremated human remains are limited by severe analytical constraints. Estimation of basic anthropological parameters such as sex of individuals or their age at death is often uncertain. A method for assessing the sex of cremated individuals measures the lateral angle of the petrous part (PP) of the temporal bone, known as the lateral angle (LA) method. In the cemetery of the Lusatian culture in Czernikowice (51.317389°N, 15.871469°E), 6 well-preserved PP were identified. The analyzed PP belonged to 6 different individuals: 3 adults and 3 children. Based on standard anthropological methods, sex was estimated for adults individuals: 2 males and 1 female. The identified PP served as the basis for application of the LA method. The bones were scanned by computed tomography (CT) and the tomographic imaging allowed measurement of the lateral angle. The absolute values of intra-observer errors did not exceed 1°. Relative technical errors of measurements (rTEM) fell in the range below 5%, which is indicative of their high precision. Individuals for which the LA value was greater than or equal to 45.0° were qualified as females and those for which it was less than 45.0° – as males. The LA values for female individuals ranged from 48.0 to 49.1°, (average 48.5±0.78°, median 48.4°) and for male individuals were in the range of 24.9-37.5° (average 33.4±5.80°, median 35.5°). The absolute difference between the average values for female and male individuals was considerable (15.1°) and statistically significant (p < 0.001). The LA method provides good reliability of measurements when it comes to this analysis with regard to cremated osteological material, and the use of non-invasive CT enhances its value in the context of archaeological remains. However, its capability for sexing subadult individuals should be approached with caution and requires further research.